The genetic mechanisms underlying the convergent evolution of pollination syndromes in the Neotropical radiation of Costus L. - Valderrama, Eugenio; Landis, Jacob B.; Skinner, Dave; Maas, Paul J. M.; Maas-van de Kramer, Hiltje; André, Thiago; Grunder, Nikolaus; Sass, Chodon; Pinilla-Vargas, Maria; Guan, Clarice J.; Phillips, Heather R.; Almeida, Ana Maria Rocha de; et al. (Frontiers in Plant Science, 2022)
Selection together with variation in floral traits can act to mold floral form, often driven by a plant’s predominant or most effective pollinators. To investigate the evolution of traits associated with pollination, we developed a phylogenetic framework for evaluating tempo and mode of pollination shifts across the genus Costus L., known for its evolutionary toggle between traits related to bee and bird pollination. Using a target enrichment approach, we obtained 957 loci for 171 accessions to expand the phylogenetic sampling of Neotropical Costus. In addition, we performed whole genome resequencing for a subset of 20 closely related species with contrasting pollination syndromes. For each of these 20 genomes, a high-quality assembled transcriptome was used as reference for consensus calling of candidate loci hypothesized to be associated with pollination-related traits of interest. To test for the role these candidate genes may play in evolutionary shifts in pollinators, signatures of selection were estimated as dN/dS across the identified candidate loci. We obtained a well-resolved phylogeny for Neotropical Costus despite conflict among gene trees that provide evidence of incomplete lineage sorting and/or reticulation. The overall topology and the network of genome-wide single nucleotide polymorphisms (SNPs) indicate that multiple shifts in pollination strategy have occurred across Costus, while also suggesting the presence of previously undetected signatures of hybridization between distantly related taxa. Traits related to pollination syndromes are strongly correlated and have been gained and lost in concert several times throughout the evolution of the genus. The presence of bract appendages is correlated with two traits associated with defenses against herbivory. Although labellum shape is strongly correlated with overall pollination syndrome, we found no significant impact of labellum shape on diversification rates. Evidence suggests an interplay of pollination success with other selective pressures shaping the evolution of the Costus inflorescence. Although most of the loci used for phylogenetic inference appear to be under purifying selection, many candidate genes associated with functional traits show evidence of being under positive selection. Together these results indicate an interplay of phylogenetic history with adaptive evolution leading to the diversification of pollination-associated traits in Neotropical Costus.